EP459 Clinical management of ovarian masses in pregnancy. (1st November 2019) - Mascilini, F; Quagliozzi, L; Moro, F; Palumbo, AR; Peterlunger, I; Testa, AC; Scambia, G; Fagotti, A
Abstract : Introduction/Background: The number of women diagnosed with ovarian masses during pregnancy has increased in recent years and the management of these women is controversial. Methodology: To describe the diagnostic-accuracy of US in the differential diagnosis ovarian masses diagnosed during pregnancy. This is a retrospective single center study, approved by the local IRB. Clinical charts of pregnant women examined at our gynecologic oncology ultrasound center between 2000 and 2019 for a suspicious adnexal mass were retrieved. Ultrasound characteristics of the masses were described by using International Ovarian Tumor Analysis (IOTA) terminology. Results: 98 patients with an ovarian mass during pregnancy were found. Fifty-five women (56.1%) underwent close US monitoring each four weeks until delivery and one month after delivery. The remaining 43 cases (43.9%) underwent surgery for either high suspicious of malignancy, or high risk of side effects such as torsion, rupture or obstacle to pregnancy. Among them, 14 (32.5%) had a malignant tumor (10 primary ovarian and 4 metastatic tumor to the ovary), 17 (39.5%) had borderline ovarian tumor (4 mucinous and 13 serous histotype), 12 (28.0%) had a benign ovarian disease. At ultrasound, papillary projections were present in 16 of 31 malignant/borderline tumors (4 primary ovarian cancer and 12 borderline) and in 4 of 12 benign masses (p=0.281). The most frequent US feature was multilocular-solid mass (12/31, 38.7%) followed by unilocular-solid (9/31, 29.1%), solid (7/31, 22.5%) and multilocular (3/31, 9.7%). Accuracy rate of US with respect to final histological diagnosis was 76.7% considering BOT as primary ovarian tumors. Conclusion: Differential diagnosis of ovarian masses during pregnancy is still challenging and clinical management needs clear US rules. Disclosure: Nothing to disclose.